Fairytale traditions in the modern world: On the margins of the II Forum for Researchers of Belarusian Fairy Tales - Valodzina, Tatsiana; Marmysh, Tatsiana (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Discussion on: II Forum for Researchers of Belarusian Fairy Tales (Minsk, May 27–29, 2021).